2004
DOI: 10.1016/j.jacc.2004.05.083
|View full text |Cite
|
Sign up to set email alerts
|

Effect of granulocyte-macrophage colony-stimulating factor inducer on left ventricular remodeling after acute myocardial infarction

Abstract: The GM-CSF induction by romurtide facilitated infarct expansion in association with the promotion of monocyte recruitment and inappropriate collagen synthesis in the infarcted region during the early phase of MI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
78
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(82 citation statements)
references
References 30 publications
4
78
0
Order By: Relevance
“…For RT-PCR analysis, pats were sacrificed at 3 hours, 6 hours, 12 hours, 1 day, 2 days, 7 days, 14 days, or 28 days post-MI and sham-operated rats served as controls (n=6 at each time point). In vivo ischemia and reperfusion (I/R) was induced as we previously described [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19].…”
Section: Experimental Myocardial Infarctionmentioning
confidence: 99%
See 2 more Smart Citations
“…For RT-PCR analysis, pats were sacrificed at 3 hours, 6 hours, 12 hours, 1 day, 2 days, 7 days, 14 days, or 28 days post-MI and sham-operated rats served as controls (n=6 at each time point). In vivo ischemia and reperfusion (I/R) was induced as we previously described [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19].…”
Section: Experimental Myocardial Infarctionmentioning
confidence: 99%
“…Toeda et al, Versican expression in myocardial infarction 11 To test that GM-CSF induced inflammatory cytokine release in PBMC, we finally examined the production of inflammatory cytokines, IL-6 and MCP-1, in GM-CSF-stimulated PBMC by ELISA. GM-CSF induced both IL-6 and MCP-1 in PBMC in a dose-dependent manner ( Fig.…”
Section: Gm-csf Induced Cytokine Production In Human Pbmcmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, MCSF is a marker of inflammation, this finding reinforce the hypothesis that inflammation is the common pathway of ACS, which mainly differs in the degree of thrombosis, that may be occlusive and persistent leading to STEMI or transient leading to NSTEMI and not in the pathophysiological background. (22) …”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that GM-CSF promotes the infiltration of monocytes and macrophages after tissue injury (34,35). Furthermore, GM-CSF mRNA and protein synthesis occurs in both monocytes and endothelial cells as a result of direct cell-to-cell interaction (36).…”
Section: Discussionmentioning
confidence: 99%